THE IMPACT OF MOBILE APPLICATIONS ON INDEPENDENT ENGLISH LEARNING IN UZBEK UNIVERSITIES - Zokirova Marjona Xislatjon qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Annotation: This paper investigates the influence of mobile applications on independent English language learning among students at Uzbek universities. It explores how language-learning apps such as Duolingo, Memrise, BBC Learning English, and Quizlet contribute to vocabulary acquisition, listening comprehension, and grammar improvement outside the classroom. The study is based on surveys, interviews, and observational data gathered from university students who actively use mobile apps for autonomous learning. The findings reveal that mobile-assisted language learning (MALL) increases learners' motivation, flexibility, and engagement, making it a valuable supplement to traditional instruction in Uzbekistan’s higher education system.